Aberrant mitochondrial function in patient-derived neural cells from CDKL5 deficiency disorder and Rett syndrome. (13th September 2019) - Jagtap, Smita; Thanos, Jessica M; Fu, Ting; Wang, Jennifer; Lalonde, Jasmin; Dial, Thomas O; Feiglin, Ariel; Chen, Jeffrey; Kohane, Isaac; Lee, Jeannie T; Sheridan, Steven D; Perlis, Roy H
Abstract: The X-linked neurodevelopmental diseases CDKL5 deficiency disorder (CDD) and Rett syndrome (RTT) are associated with intellectual disability, infantile spasms and seizures. Although mitochondrial dysfunction has been suggested in RTT, less is understood about mitochondrial function in CDD. A comparison of bioenergetics and mitochondrial function between isogenic wild-type and mutant neural progenitor cell (NPC) lines revealed increased oxygen consumption in CDD mutant lines, which is associated with altered mitochondrial function and structure. Transcriptomic analysis revealed differential expression of genes related to mitochondrial and REDOX function in NPCs expressing the mutant CDKL5 . Furthermore, a similar increase in oxygen consumption specific to RTT patient–derived isogenic mutant NPCs was observed, though the pattern of mitochondrial functional alterations was distinct from CDKL5 mutant–expressing NPCs. We propose that aberrant neural bioenergetics is a common feature between CDD and RTT disorders. The observed changes in oxidative stress and mitochondrial function may facilitate the development of therapeutic agents for CDD and related disorders.